PENYELESAIAN WANPRESTASI DALAM PEJANJIAN JUAL BELI PERUMAHAN ANTARA PENJUAL PT. CAHAYA MERANTI INTERNASIONAL (CMI) DENGAN PEMBELI DI KE KEPULAUAN MERANTI - Jeni Desfa Junita; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Non-perfomance of contract is a condition where one or both parties bound in an agreementnot carrying out obligations or achievements according to what is written in the agreementthat has been agreed upon. In this case, the seller or the housing developer named PT.Cahaya Meranti Internasional (CMI), committed a Non-perfomance of contract against thebuyer (member of the Meranti Islands community). In this case, the seller does not return thefunds deposited to them, while based on the agreement the funds deposited by the buyershould be returned up to 100% excluding administrative fees if the mortgage applicationsubmitted is rejected by the bank. This study aims to determine the Implementation of theHousing Purchase Agreement between the Seller and the Buyer and to find out the legalremedies for the Housing Buyer in Requesting a Refund Against the Seller who Admitted Non-perfomance of contract.The type of research used by the writer is sociological research where the writerdirectly conducts research at the location or place under study to provide a complete andclear picture of case. The population and sample in this study are Marketing Supervisors atPT. CMI and Housing Buyers in the Meranti Islands.The results of the analysis in this study show that the implementation of the housingbuy and purchase agreement between the seller and the buyer is not carried out properly inaccordance with the agreement. The failure in following the agreement was caused by Non-perfomance of contract comitted by the seller, in which case the seller should return the fundsthat have been deposited in full if the buyer submits a cancellation, if the reason for thecancellation is due to a refusal of credit from the Bank. Until now, the seller has not fulfilledits obligation in returning the initial deposit from the buyer, which has resulted significantlosses experienced by the buyer. As a solution, the buyer have used legal efforts in form ofthe dispute resolution method outside the court for requesting a refund from the seller, PT.CMI, who admitted the Non-perfomance of contract. Moreover, the buyer has made efforts tonegotiate with the assistance and mediation from the Meranti Resort Police. However, theseller did not carry out the results of the deliberations as they shouldKeywords: Non-perfomance of contract, Sale and Purchase Agreement, Housing